2002
DOI: 10.1083/jcb.200203050
|View full text |Cite
|
Sign up to set email alerts
|

Retention of a cell adhesion complex at the paranodal junction requires the cytoplasmic region of Caspr

Abstract: An axonal complex of cell adhesion molecules consisting of Caspr and contactin has been found to be essential for the generation of the paranodal axo-glial junctions flanking the nodes of Ranvier. Here we report that although the extracellular region of Caspr was sufficient for directing it to the paranodes in transgenic mice, retention of the Caspr–contactin complex at the junction depended on the presence of an intact cytoplasmic domain of Caspr. Using immunoelectron microscopy, we found that a Caspr mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
98
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 49 publications
11
98
0
Order By: Relevance
“…The Nf186 cDNA construct was a gift from Dr. Vann Bennett (Duke University, Durham, NC) (34). Nf155-Fc and Cn-Fc cDNA constructs were provided by Dr. Elior Peles (Weizmann Institute, Rehovot, Israel) (35,36). The Cn and Cn Ig -Fc constructs were gifts from Dr. Genviève Rougon (Laboratoire de Génétique et Physiologie du Dével-oppement, Marseille, France) (37).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nf186 cDNA construct was a gift from Dr. Vann Bennett (Duke University, Durham, NC) (34). Nf155-Fc and Cn-Fc cDNA constructs were provided by Dr. Elior Peles (Weizmann Institute, Rehovot, Israel) (35,36). The Cn and Cn Ig -Fc constructs were gifts from Dr. Genviève Rougon (Laboratoire de Génétique et Physiologie du Dével-oppement, Marseille, France) (37).…”
Section: Methodsmentioning
confidence: 99%
“…The next morning, cells were washed with PBS and fixed with 4% paraformaldehyde. The cells were washed twice with PBS, followed by blocking with PBS containing 1% glycine and 10% goat serum (PBGG) for 30 min at room temperature as previously described (35). Primary antibodies were diluted in PBGG and incubated for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NCP1 is the only identified AGJ axonal protein that contains a cytoplasmic domain. Evidence gathered from biochemical and transgenic mice studies showed that the cytoplasmic domain of NCP1 binds to the actin-spectrin binding protein 4.1B (27,28). There is growing realization that NCP1 mediates AGJ interactions with the axonal cytoskeleton and may participate in axon-glial signaling; however, physiological evidence to support these assumptions remains to be established.…”
mentioning
confidence: 97%
“…Immunocytochemistry and immunohistochemistry were performed as described previously (Poliak et al, 2003). The following antibodies were used: mouse anti-GFAP (Sigma), rat anti-MBP (Chemicon, Temecula, CA), mouse anti-CNP (2Ј,3Ј-cyclic nucleotide 3Ј-phosphodiesterase) (Sigma), mouse anti-␤-tubulin IV (Sigma), rabbit anti-Caspr (Gollan et al, 2002), hybridoma supernatants of mouse antibodies to RIP, O4, Ran2, A2B5, and mouse anti-myelin oligodendrocyte glycoprotein (MOG) Z12 (generous gift from N. Schaeren-Wiemers, University Hospital Basel, Basel, Switzerland). Immunoelectron microscopy was performed as described previously (Gollan et al, 2002).…”
Section: Plasmids and Antibodiesmentioning
confidence: 99%